2020
DOI: 10.9734/jamb/2020/v20i530244
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Assessment of Bed Linens in Ekiti State University Students’ Hostels

Abstract: Bed linen is clearly recognized as a potential reservoir for microorganisms and could be a vector of disease transmission. The present study was aimed at isolating and characterizing bacteria and fungi from different kinds of bed linen of student in Ekiti State University hostels. Pour plate method was used for the enumeration of total bacteria count from the posterior and anterior end of the bed linen. The average bacteria count for the anterior and posterior end was 7.46 and 7.16 Log10 CFU/ml respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As in this study, multiple resistance to commonly used antibiotics has been reported in several microorganisms, including Escherichia and Staphylococcus species, isolated from bed linens of university students (Olowomofe et al, 2020). Bed linens used in other settings, such as hospitals, nursing homes, and the larger community, have also been identified as potential sources of pathogenic microorganisms (Okareh, 2018;Pinon et al, 2013;Bloomfield et al, 2011).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…As in this study, multiple resistance to commonly used antibiotics has been reported in several microorganisms, including Escherichia and Staphylococcus species, isolated from bed linens of university students (Olowomofe et al, 2020). Bed linens used in other settings, such as hospitals, nursing homes, and the larger community, have also been identified as potential sources of pathogenic microorganisms (Okareh, 2018;Pinon et al, 2013;Bloomfield et al, 2011).…”
Section: Discussionmentioning
confidence: 59%
“…From the bed linens of 23 undergraduate students, 9 bacterial isolates were obtained, including strains of S. aureus (7) and E. coli (2). Antibiotic susceptibility testing revealed that a significant number of the isolates were resistant to cefuroxime, ceftazidime, cefixime, nitofurantoin, erythromycin, and augmentin (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations